Crisis Communication of Pekalongan City Communications and Informatics Department Towards The Community of North Pekalongan In Handling Rob Floods - Sekar Fitri Karomah; Apriliani , Riski (Jogjakarta Communication Conference (JCC), 2024)
BPBD monitored tidal floods in Pekalongan City occurred in almost all areas in North Pekalongan as high as 50-80 centimeters. The impact of this crisis also very worrying, many houses and families are left without a place to live. In this case of crisis, local government required to have an effective crisis strategy especially in handling the crisis communication because this crisis have not handled properly. This research aims response and communication strategy of the local government in dealing with this crisis that occurred base on the strategy analysis of Situational Crisis Communication Theory (SCCT). This research construct the theory from Timothy W. Coombs which will look at the response, and strategy from local government to people’s. The method of this research is case study with data collection through depth-interview. This research use triangulation data from Miles and Huberman, collection data using documentation, observation, and interview. Our research shows that the important thing in handling crisis that is still lacking from local government is involvement the people’s in a forum before implementing a strategy. This point has a negative effect on the sustainability of the strategy because it often causes people’s to misunderstand in next crisis situation. However, one local government strategy that has been successful is empathetic narratives that build people’s awareness to local government.